PERAN SUAMI TERHADAP TINGKAT KECEMASAN IBU HAMIL DALAM MENGHADAPI PERSALINAN NORMAL - Ramini Harahap, Novy; Nurrahmaton, Nurrahmaton; Era Liesmayani, Elvi; Wahyuni, Sri (AHM Center, 2023)
Pregnant women will feel a variety of changes, both physically and mentally. Anxiety is a vague feeling of relaxation due to discomfort or fear accompanied by a response. This condition will increase the number of labor complications such as bleeding and infection that will cause an increase in maternal mortality. was to know the influence of husband’s role on the level of anxiety of pregnant women in normal facing normal labor at Bidan praktik Mandiri Nurul Hadi AR Pandrah Sub-District of Bireuen District in 2019. The type of this research was an analytical survey with cross sectional approach. This research was done at Bidan Praktik Mandiri Nurul Hadi AR, Pandrah Sub-district, Bireuen district from February to April 2019. The data collection in this study used primary record data. The data analysis used univariate and bivariate analysis with chi square test (0.05). Based on the results of the study, it was known that the majority of husbands in the category of less than 21 people (70.0%), the anxiety of the majority of third trimester pregnant women with the category of anxiety as many as 19 people (63.3%) with mild anxiety. Based on OR values ​​obtained 14,875 (95% CI 2,198-100,656). there is the influence of the husband's role 15 times to the anxiety of third trimester pregnant women in facing normal Labor at Bidan Praktik Mandiri Nurul Hadi AR Pandrah Sub-District Bireuen District in 2019. It is suggested to couples, especially husbands, to provide support mothers in order to reduce anxiety in pregnant women in the third trimester so that labor that will be faced can run smoothly.